2021
DOI: 10.1152/ajprenal.00628.2020
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lactate dehydrogenase A and B isoforms in the mouse kidney

Abstract: Cellular metabolic rates in the kidney are critical for maintaining renal function. In a hypoxic milieu, cells rely on glycolysis to meet energy needs, resulting in the generation of pyruvate and NADH. In the absence of oxidative phosphorylation, the continuation of glycolysis is dependent on the regeneration of NAD+ from NADH accompanied by the fermentation of pyruvate to lactate. This reaction is catalyzed by lactate dehydrogenase (LDH) isoform A (LDHA), while isoform B (LDHB) catalyzes the opposite reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…A recent publication from our group has shown the differential expression of lactate dehydrogenase isoform A (LDHA) and isoform B (LDHB) throughout the nephron (2). We observed that LDHA, which drives the conversion of pyruvate to lactate, is strongly expressed in the proximal parts of the nephron, whereas LDHB, which drives the opposite reaction, is predominant in the distal parts of the nephron (2).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…A recent publication from our group has shown the differential expression of lactate dehydrogenase isoform A (LDHA) and isoform B (LDHB) throughout the nephron (2). We observed that LDHA, which drives the conversion of pyruvate to lactate, is strongly expressed in the proximal parts of the nephron, whereas LDHB, which drives the opposite reaction, is predominant in the distal parts of the nephron (2).…”
mentioning
confidence: 65%
“…Multiple recent studies have transformed the perspective for lactate metabolism from being a static byproduct of glycolysis into a much more sophisticated molecule with roles ranging from an energy carrier to a signaling molecule (1). A recent publication from our group has shown the differential expression of lactate dehydrogenase isoform A (LDHA) and isoform B (LDHB) throughout the nephron (2). We observed that LDHA, which drives the conversion of pyruvate to lactate, is strongly expressed in the proximal parts of the nephron, whereas LDHB, which drives the opposite reaction, is predominant in the distal parts of the nephron (2).…”
mentioning
confidence: 99%
“…Much like the lactate shuttle hypothesis proposed by Osis et al (1), the hypotheses proposed by Dr. Bankir are intriguing and require validation through animal experiments. Luckily, recent advances in molecular biology may provide the tools to answer these important questions.…”
mentioning
confidence: 97%
“…In a letter to the Editor of the American Journal of Physiology-Renal Physiology, prompted by a recent publication by Osis et al (1) and a companion Editorial by Sheikh-Hamad (2), Dr. Bankir introduces the premise of an intrarenal Cori cycle. The Cori cycle describes the movement of lactate from the peripheral tissues, such as the muscle, to the liver, where it is converted to pyruvate by lactate dehydrogenase.…”
mentioning
confidence: 99%
“…In their recent study, Agarwal and colleagues showed how two forms of lactate dehydrogenase are distributed within the renal cortex and how they are affected by hypoxia (1). In the accompanying Editorial, David Sheikh-Hamad emphasized the importance of this "kidney lactate shuttle" (2).…”
mentioning
confidence: 99%